THE ANALYSIS OF LANGUAGE STYLE USED IN “SISTERS COURSE” - Widyaiswara, Tiara; Nurman, Moh.; Khotimah, Anisul (Universitas PGRI Sumatera Barat, 2022)
This study aims to find out the type of language style that students use to communicate in the